Dakwah Sebagai Media Integrasi Agama dan Ilmu Pengetahuan - Dini Maulina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to look further at science and religion and da'wah as a medium for the integration of both. Da'wah with one of its goals, namely spreading truth and goodness can be one of the media to explain that science and religion are not contradictory and both have the same goal, namely to seek the essence of truth. This study uses a library research approach by analyzing two variables, namely science and religion by utilizing books, journals, and other library tools as references and sources of data or information. Based on the results of the analysis, it is found that one conclusion is that science and religion do not contradict each other. Both science and religion both require the role of reason to understand it perfectly and da'wah can be a medium to convey the harmony of the objectives of the two variables.